AN ANALYSIS OF BURNOUT SYNDROME AND COMMUNICATION WITHIN THECULTURE OF PATIENT SAFETY - Sri Hananto Ponco; Puguh Widiyanto (Program Studi Ilmu Keperawatan Universitas Jember, 2025)
Background: the implementation of patient safety standards is essential to minimizing and preventing errors and harm to patients. Two key factors in fostering a culture of patient safety are the presence of burnout syndrome and the effectiveness of communication among nursing professionals. Objective: this study aimed to identify the prevalence of burnout syndrome and assess communication practices within the context of patient safety culture. Methods: a descriptive-analytic study with a cross-sectional design was conducted involving 54 respondents selected through purposive sampling. Data were collected in a hospital in Magelang City using the Copenhagen Burnout Inventory (CBI) and the Hospital Survey on Patient Safety Culture (HSOPSC). Data were analyzed using mean and frequency distribution. Results: the analysis revealed that 25.9% of nurses experienced burnout syndrome, while 74.1% did not. The mean score for communication within the patient safety culture was 3.78 out of a maximumscore of 5. Conclusion: the majority of nurses did not experience burnout syndrome, and communication within the patient safety culture was categorized as moderately good.